THE INFLUENCE OF POLITICAL BACKGROUND ON LEGISLATIVE CANDIDATES’ ELECTABILITY: THE MODERATING ROLE OF PUBLIC TRUST: PENGARUH LATAR BELAKANG POLITIK TERHADAP KELAYAKAN CALON ANGGOTA LEGISLATIF: PERAN MODERATOR KEPERCAYAAN MASYARAKAT - Andi Hartati; risman sarifudin (Jurnal Kebijakan dan Pelayanan Publik, 2026)
This study examines the extent to which candidates’ political background influence their electability in local legislative elections, specifically within the context of the 2024 elections in Banggai Regency, Indonesia. The study further investigates how public trust moderates this relationship, offering insight into interplay between candidate characteristic and voter perceptions. This study employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the realtionship among political background, public trust, and candidate electability. The analysis of data from 100 respondents using PLS-SEM reveals that political background has a significant posirive effect on candidate electability , while public trust also exterts a direct and significant influnce . furthermore, public trust significantly moderates the relationship between political background and electability , suggesting that candidates with strong political credential receive greater electoral support when they are perceived as trustworthy. The model explain 56% of the variance in electability. , with all contructs meeting the trhesholds for realibility and validity. the findings of this study offer several prcatical implications for political actors, campaign strategist, and political parties operating within local electoral contexts. This study offers a significant contribution to the literature on electoral behaviour and political marketing by elucidating the interactive influence of structural attributes (political background) and perceptual dimensions (public trust) on candidate electability.